Comparison of the Crossbreeding Effects of Three Mandarin Fish Populations and Analyses of the Microsatellite Loci Associated with the Growth Traits of F1 Progenies - Qingkai Zeng; Chengfei Sun; Junjian Dong; Yuanyuan Tian; Xing Ye (International Journal of Aquaculture and Fishery Sciences - Peertechz Publications, 2017)
Cross breeding with different populations might lead to heterosis and enhance the genetic diversity of the resulting offspring. In this study, three populations of mandarin fish (Siniperca chuatsi), including two cultured (A and B) and one wild population (C), were used to construct three pure groups (A♂×A♀, B♂×B♀, C♂×C♀) and six crossbred groups (A♂×B ♀, A♂×C♀, B♂×A♀, B♂×C♀, C♂×A♀, C♂×B♀). Growth performance was compared among all combinations, and 11 microsatellites were used to analyze the genetic diversity of the resulting offspring and identify correlations associated with growth traits (body weight, total length, and body height). The best growth performance values associated with the growth traits were detected in the progeny of the inbred A♂×A♀ group. The A♂×B♀ and A♂×C♀ F1 exhibited relatively high increases of growth in all crossbreed combinations, whereas the F1 of C♂×B♀ exhibited lower growth performance. Cross combinations that used male fi sh from the A population displayed significant growth advantages. Analysis of genetic diversity showed that the expected heterozygosity (He) of the F1 of all combinations were greater than 0.5 except A♂×C♀, B♂×A♀, and A♂×A♀. The results of association analyses indicated that seven microsatellite loci, est21, w19521, sch14, sc90, est43, w19517, and sc01 were associated with the targeted growth traits. This result laid a good foundation for further breeding selection of mandarin fish using population selection and molecular marker-assisted selection. It also would provide more reliable guidelines for breeding selection of other fish species.